Kebijakan Surat Izin Mengemudi (SIM) Seumur Hidup: Tantangan dan Peluang di Indonesia - Dianawati, Nur; Sari, Jayanti Armida (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
The Lifetime Driver's License Policy has sparked debate in Indonesia. This research examines the challenges and opportunities of implementing a lifetime driving license policy in Indonesia. This study employs literature as a fundamental technique for comprehensive understanding; the research utilizes the SOAR analysis approach to formulate implementation strategies. This study concludes that the implementation of a lifetime driver's license policy has substantial potential to enhance administrative efficiency, reinforce service integrity, promote public awareness and adherence to traffic regulations, and contribute to overall road safety improvements. The recommended strategies include fostering service transparency, strengthening supervision and law enforcement, digitalizing service processes, raising public awareness through socialization and education, enhancing service quality, improving driver competence through training, streamlining bureaucratic procedures, and actively involving the community.